Learning Who Knows What: Children Adjust Their Inquiry to Gather Information from Others - Mills, Candice M.; Landrum, Asheley R. (Frontiers in Psychology, 2016)
The current research focuses on how children’s inquiry may be affected by how they learn about which sources are likely to provide accurate, helpful information. Four- and 5-year-olds (N = 188) were tasked with asking two different puppet informants – one knowledgeable and one not knowledgeable – questions to determine which of four pictures was inside of a set of boxes. Before beginning the task, children learned about the knowledge status of the two informants in one of three learning conditions: a) by witnessing how the informants answered sample questions (i.e., show condition), b) by being told what informants knew (i.e., tell condition), or c) by both (i.e., show & tell condition). Five-year-olds outperformed 4-year-olds on most parts of the inquiry process. Overall, children were less certain about which informant had been most helpful when they found out that information solely via observation as compared to when they had some third-party information about the informant knowledge. However, children adjusted their questioning strategies appropriately, more frequently asking questions that served to double check the answers they were receiving in the observation only condition. In sum, children were highly resilient, adjusting their questioning strategies based on the information provided, leading to no overall differences in their accuracy of determining the contents of the boxes between the three learning conditions. Implications for learning from others are discussed.